ANALISIS FAKTOR ATAS KEPUTUSAN MEMILIH ANGGOTA LEGISLATIF DI KABUPATEN JEMBER (Studi Pada Pemilih Partai Gerindra Kabupaten Jember) - mirhabun nadir (MAGISTER MANAJEMEN UNISMA, 2020)
Democracy as a process has formed the spirit of equality and togetherness in advance in politics, among the many parties democracy elected candidates for legislative members is one that has important meaning in because in this legislative elections in the community given many personal alternatives that have different qualifications For Become vice and fight for their aspirations.Unlike pilpres or pilkada that can choose the decision (ekskutif) then the legislative elections choose the policy controller (legislative), and from the legislative function as a controller of this decision also includes the function of budget compilers (budgeting)The policy of organizing politics in Indonesia provides an opportunity for the people to enjoy a democracy, but problems arise as part of the political dynamic becomes a challenge for organizers to offer a proportional and fair system.The election process of legislative members is not maintained from the very tough competition because of the many tricks done to influence the sympathy of the community and to win as many votes as possible in order to be elected as members of the legislature.In response to the phenomenon it is necessary in the know and examined factors ketokohan factors as factors that greatly influence the decision of choosing.The popularity factor will also have a psychological impact on voters, with the popularity of legislative candidates then it is likely to choose to have a large enough percentage.Educational factors can not be excluded as part of factors that will contribute to legislative candidates to weigh in the parliament. The politics of money that gets the stigma of the assemblies in the political dynamics of financial power can not simply be put aside as forces that can influence the choice in determining the choice of their representativesThese four factors are selected based on empirical experience which will influence voters' attitudes in determining their choice in the election of legislative members in Jember district. Keywords: Influence, legislative, election